2018
DOI: 10.1186/s40337-017-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Group schema therapy for eating disorders: study protocol

Abstract: BackgroundThe treatment of eating disorders is a difficult endeavor, with only a relatively small proportion of clients responding to and completing standard cognitive behavioural therapy (CBT). Given the prevalence of co-morbidity and complex personality traits in this population, Schema Therapy has been identified as a potentially viable treatment option. A case series of Group Schema Therapy for Eating Disorders (ST-E-g) yielded positive findings and the study protocol outlined in this article aims to exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…Due to the objectives of the study, the relationship between BMI and the intensities of restrictive, compulsive, and bulimic behaviors were not analyzed. On the other hand, Saleh et al [ 76 ], conducting a study using the Eating Attitudes Test (EAT 26) on a population of 2001 students at the An-Najah National University in Palestine, indicated a significant positive relationship between BMI and restrictive and bulimic behaviors. The surveyed female students obtained better results than female students of science and medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the objectives of the study, the relationship between BMI and the intensities of restrictive, compulsive, and bulimic behaviors were not analyzed. On the other hand, Saleh et al [ 76 ], conducting a study using the Eating Attitudes Test (EAT 26) on a population of 2001 students at the An-Najah National University in Palestine, indicated a significant positive relationship between BMI and restrictive and bulimic behaviors. The surveyed female students obtained better results than female students of science and medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The surveyed female students obtained better results than female students of science and medicine. Saleh et al [ 76 ] did not compare Palestinian women with women of other nationalities, and age was significantly and negatively correlated with the results of the EAT-26 test in terms of describing restrictive and bulimic eating behaviors. As indicated by Izydorczyk et al [ 32 ], in studies conducted on Polish and Japanese women, the latter (similarly to the Vietnamese women in the research by Izydorczyk and the team presented in this article) showed a higher level of compulsive and bulimic behaviors than Polish women.…”
Section: Discussionmentioning
confidence: 99%
“…SWC functions as a driving force of engaging in binging when encountering high-calorie food, specifically working as a moderator of craving ( 10 , 11 , 14 , 15 ). People with SWC who have high concern on eating high-calorie food are continually driven to binge due to prepossession with palatable foods ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this search no treatments targeting eating disorders specifically were found to exist [14], despite the movement of this area into the spotlight over 10 years ago [15]. Most treatments of people with a high BMI in bipolar disorder neglect psychological factors with the exception of [16], and people with bipolar disorder are often though not always; see [17] excluded from eating disorder treatment trials e.g. [18, 19].…”
Section: Introductionmentioning
confidence: 99%